DFT band alignment of polar and nonpolar GaN/MgGeN2, ZnO/MgGeN2 and GaN/ZnO heterostructures for optoelectronic device design - Chaiyawat Kaewmeechai (2020)
© 2020 Elsevier B.V. We calculated the band alignment among MgGeN2, ZnO and GaN compounds using density functional theory (DFT) calculations. The norm-conserving pseudopotentials approach was performed to determine the band gap of each compound. The band offsets at the interfaces of GaN/MgGeN2 and ZnO/MgGeN2 were calculated from the differences in the bulk band edges including the interfacial dipole-potentials. Moreover, the effect of strain was also investigated to govern the lattice mismatches between MgGeN2 and substrates (i.e. GaN and ZnO). We found that the band alignment of nonpolar heterojunctions is type-I for GaN/MgGeN2 and type-II for ZnO/MgGeN2 respectively. From these results, the band offsets of GaN/ZnO were extracted by using transitivity rule and confirmed with the direct calculation. Moreover, the polar band offsets shift from nonpolar ones and change the band alignment of ZnO/MgGeN2 with (Mg,Ge)-O interface to type-I. These calculated band alignments present the potential of using MgGeN2 in optoelectronic applications as an electron blocking layer for ZnO-based UV-LED and a quantum-well barrier for ZnO and GaN-based UV laser diode.